2008
DOI: 10.1159/000151566
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Effects of Variable Work Shifts on Quality of Sleep, General Health and Work Performance

Abstract: Objectives: The aim of this study was to explore the detrimental effects of working a varying pattern of 8-hour shifts on quality of sleep, general health and work performance. Subjects and Methods: The Arabic version of the Pittsburgh Sleep Quality Index (PSQI)and 2 self-administered questionnaires were used to assess quality of sleep, work performance and general health in a sample of 200 males on a schedule of varying 8-hour shifts at the Kuwait Oil Company. A matched sample of an equal number of workers on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 29 publications
2
32
0
4
Order By: Relevance
“…However, some researchers demonstrated that smoking, drinking tea, coffee, and alcoholic beverages are more common among shift workers than day workers (39,40). In these studies, the sample size of the study was much bigger than ours.…”
Section: Discussionmentioning
confidence: 54%
“…However, some researchers demonstrated that smoking, drinking tea, coffee, and alcoholic beverages are more common among shift workers than day workers (39,40). In these studies, the sample size of the study was much bigger than ours.…”
Section: Discussionmentioning
confidence: 54%
“…Además se obtiene un aumento de errores profesionales y accidentes relacionados, en el mismo turno 7,9 . En nuestro estudio la capacidad de conciliación de un sueño reparador no ha mostrado diferencias entre turnos pero sí la presencia de fatiga.…”
Section: Discussionunclassified
“…Se ha demostrado que tiene un efecto sobre el equilibrio del organismo por desfase de los ritmos biológicos (ritmo circadiano [5][6] y patrón de sueño 7 ). Asimismo, influye en la vida social y familiar, ya que los horarios de trabajo interfieren directamente con las actividades de ocio, las obligaciones domésticas y otros quehaceres de la vida cotidiana.…”
Section: Introductionunclassified
“…Shift work is an employment practice designed to make use of, or provide service, all 24 hours of the clock each day of the week, also known as 24/7 [1].The data from the National Health Interview survey Occupational Health Survey,29 % of all U.S. workers in 2010 worked as an alternative shift(not a regular day shift [2],15% of workers worked the night shift regularly [3].Among all occupations, food preparations, and serving occupations had the highest prevalence of working an alternative shift(63%) [2].Shift work has also been traditional in law enforcement and armed forces military personnel, pilots and others that regularly change time zones while performing shift work experience jet lag and consequently suffer sleep disorders [4].The high prevalence of short sleep duration was reported by night shift workers in the transportation and warehousing(69.7%) and health -care and social assistance(52.3%) industries [5].Shift work increases the risk for the development of many disorders(health disorders) includes: risk of diabetes type 2,women on night shifts have 48% increased risk of developing breast cancer [,4,6,7].alteration of circadianrhythm, melatonin suppression [8],the WHO listed shift work that involves circadian disruption as a possible carcinogen[9,],Shift work also increases the risk of developing cluster headaches, heart attacks[110],fatigue, stress, sexual dysfunction [12],depression [13],obesity [4,],metabolic disorders, gastrointestinal disorders, musculoskeletal disorders and reproductive disorders [7]. Prevention include management practices, shift system, shift schedule shiftplan, and better management [14,15].The paper reviews the health disorders of shift workers, and preventive measures.…”
Section: Introductionmentioning
confidence: 99%